Social Media's Influence on Political Participation: Insights from a Systematic Review and Meta-Analysis in Indonesian Psychology - Kurniawan, Wawan; Arham, Muhammad; Muluk, Hamdi (Faculty of Psychology, Universitas Gadjah Mada, 2024)
This systematic review and meta-analysis examine the impact of social media on political participation. It explores whether social media functions merely as an echo chamber for pre-existing beliefs or as a dynamic tool for political engagement. Sixteen studies, involving 33,257 participants, were selected and synthesized after applying inclusion criteria and conducting multiple filtering stages. The findings reveal that, while social media can enhance political participation, its effectiveness is highly context-dependent, and its overall impact is moderate. This suggests that social media is not transformative but rather supports existing political behaviors. For Indonesian psychological research, these insights highlight the importance of considering local socio-political contexts when analyzing social media's role. Future studies should investigate the socio-cultural moderators affecting this relationship in Indonesia to inform the development of more effective political communication strategies through social media. This study contributes to the discourse on digital platforms' role in political dynamics, particularly in diverse democratic settings like Indonesia.